The type specimens of Tachinidae (Diptera) housed in the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”, Buenos Aires - Mulieri, Pablo Ricardo (2013)
The type material of species of Tachinidae (Diptera) housed in the collection of the Entomology Division of the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia” were examined and are herein documented. The collection contains 202 type specimens consisting of 54 species described by E.E. Blanchard and 12 described by J. Brèthes. Comparison of their original descriptions with the label information reveals the existence of 24 holotypes, 1 lectotype, 141 syntypes and 36 paratypes. Complete information is given for each type, including reference to the original description, label data, and preservation condition.